(untitled) (Bangladesh Agronomy Journal, 2020)
The experiment was conducted at Sher-e-Bangla Agricultural University farm to evaluate the performance of five rapeseed and mustard varieties under two different planting techniques. The planting techniques were as conventional sowing and sowing seeds in puddle soil that assigned to the main plot and five varieties viz. Improved Tori-7, BARI Sarisha -13, BARI Sarisha -15, BARI Sarisha -16 and SAU SR-3 in the sub-plots. Almost all the studied parameters were found statistically similar under two planting techniques except siliqua length that was higher (5.51 cm) in conventional method compared to that of sowing in puddled soil (5.14 cm). The highest number of siliquae plant-1 (143.67) was obtained from BARI Sarisha -16 that was similar to SAU SR-03 (134.15) and Improved Tori-7 (116.90). The maximum1000-seed weight (4.35 g) was obtained from BARI Sarisha -16 under conventional planting method that was similar to BARI Sarisha -13 irrespective of planting methods. The maximum number of siliqua plant-1 (145.20) was found in BARI Sarisha -16 under conventional planting method that was similar to the same variety in puddle soil (142.13), SAU SR-03 in both the planting method and Improved Tori-7 in conventional method (131.20). The Improved Tori-7 variety gave the maximum seed yield (2.24 t ha-1) followed by BARI Sarisha -16 (1.96 t ha-1). The highest seed yield was given by the variety BARI Sarisha -16 in conventional planting method (2.39 t ha-1) that was similar to Improved Tori-7 variety irrespective of planting techniques. Bangladesh Agron. J. 2019, 22(1): 79-88